Seed-Specific Expression of Spider Silk Protein Multimers Causes Long-Term Stability - Weichert, Nicola; Hauptmann, Valeska; Helmold, Christine; Conrad, Udo (Frontiers in Plant Science, 2016)
Seeds enable plants to germinate and to grow in situations of limited availability of nutrients. The stable storage of different seed proteins is a remarkable presumption for successful germination and growth. These strategies have been adapted and used in several molecular farming projects. In this study, we explore the benefits of seed-based expression to produce the high molecular weight spider silk protein FLAG using intein-based trans-splicing. Multimers larger than 460 kDa in size are routinely produced, which is above the native size of the FLAG protein. The storage of seeds for eight weeks and one year at an ambient temperature of 15°C does not influence the accumulation level. Even the extended storage time does not influence the typical pattern of multimerized bands. These results show that seeds are the method of choice for stable accumulation of products of complex transgenes and have the capability for long-term storage at moderate conditions, an important feature for the development of suitable downstream processes.